Ethyl 1-(2-hydroxyethyl)-2-propyl-1H-benzimidazole-5-carboxylate - Hamzah, Nurasyikin; Ngah, Nurziana; Abd Hamid, Shafida; Abdul Rahim, Aisyah Saad (Wiley-Blackwell Publishing, Inc., 2011)
In the title compound, C15H20N2O3, the benzimidazole ring is essentially planar, with a maximum deviation from the mean plane of 0.012 (1) A ˚ . The crystal structure is stabilized by intermolecular O—H N hydrogen bonds, forming centrosymmetric dimers, which are connected in the [100] direction through weak C—H O contacts